Corn versus Barley in Finishing Diets: Effect on Steer Performance and Feeding Behavior - DelCurto-Wyffels, Hannah M. (Animals (Basel), 2021)
SIMPLE SUMMARY: A variety of feedstuffs can be used in beef cattle finishing rations. While corn has traditionally been the most popular feed ingredient in the United States, barley, which is better adapted to the growing and climatic conditions of northern latitudes, can also be utilized. This study evaluated the effects of corn and barley finishing rations on cattle performance and behavior in a feedlot system. Corn-fed steers had greater gains and heavier final live weights than barley-fed steers, however, this tended to be accompanied by greater daily intake. No differences in animal behavior were observed between barley or corn-fed steers. Thus, depending on the difference of costs associated with feeding corn or barley in a given year, barley could be a potential high-quality feed source in beef cattle finishing rations. By having a better understanding of feedlot steer performance and behavior of cattle fed either barley or corn-based diets, producers will be more equipped to make informed nutritional management decisions in feedlot production. ABSTRACT: This study evaluated the effects of barley and corn finishing rations on feedlot performance and behavior of steers. Feedlot rations in this study were comprised of a main concentrate of either corn or barley. Steers were fed in a GrowSafe system to measure individual animal intake and behavior. Weight gain, average daily gain (ADG), and gain:feed were measured for each steer. Feeding behavior including time spent eating (min/day), visits per day, time per visit (min), eating rate (g/min), intake (kg/day), and intake per visit (g) were measured for each individual. Corn-fed steers had greater ADG (p < 0.01) and heavier hot carcass weights (HCW; p < 0.01). In addition, corn fed steers had a higher yield grade than barley fed steers (p < 0.01). No treatment effects (p ≥ 0.11) were observed for time spent eating, visits per day, time per visit, eating rate, intake g/kg body weight, or intake per visit. Although corn-fed steers had a greater ADG and HCW than barley-fed steers, they tended to consume more feed (p = 0.06). Depending on the difference of costs associated with feeding corn or barley, barley could be a potential high-quality feed source in beef cattle finishing rations.